Karakteristik Terorisme dengan Bumbu Globalisasi dan Hubungannya dengan Human Security - Wicaksono, Stefanus Ari (Global and Policy Journal of International Relations, 2016)
ABSTRACTTerrorism is a threat which became terrified for all over the world. Attack by attack from terrorism always replying with condemnation by the family or victim’s friends. States and international society always mad and tired because of terrorism attack. Its impact was increasingly felt from the short term to long term, from the physical to the psychological. In this paper will examine the well of character possessed by terrorists, which is useful to know a little more about the terrorists what they were. And will explain the various impacts with case studies and theoretical explanation of the theory of Human Security. The impacts of terrorism will be expanded as well by using the phenomenon of globalization as a complement. This phenomenon helps explain terrorism relationship with the media that also have an impact, so it is not just simply look at the impact in terms of terrorism itself but also of the phenomenon of globalization along with one instrument which in this era became very heated discussion.Keywords: Human security, Terrorism, Globalization, Media, Psychological, InternationalDOI : https://doi.org/10.33005/jgp.v4i02.1916